Scalar and Ignorance Inferences Are Both Computed Immediately upon Encountering the Sentential Connective: The Online Processing of Sentences with Disjunction Using the Visual World Paradigm - Zhan, Likan (Frontiers in Psychology, 2018)
Accounts based on the pragmatic maxim of quantity make different predictions about the computation of scalar versus ignorance inferences. These different predictions are evaluated in two eye-tracking experiments using a visual world paradigm to assess the on-line computation of inferences. The test sentences contained disjunction phrases, which engender both kinds of inferences. The first experiment documented that both inferences are computed immediately upon encountering the disjunctive connective, at nearly identical temporal locations. The second experiment was designed to determine whether or not there exists an intermediate stage at which the truth of the corresponding conjunction phrase is ignored. No such stage was found.